2013
DOI: 10.1118/1.4805101
|View full text |Cite
|
Sign up to set email alerts
|

Lung sparing and dose escalation in a robust‐inspired IMRT planning method for lung radiotherapy that accounts for intrafraction motion

Abstract: A 4D dose calculation based on deformable image registration was used to evaluate a robust-inspired planning strategy for lung radiotherapy. This method offers notable reductions to lung dose while improving tumor coverage through the use of reduced geometric margins combined with edge enhancements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…In this study, each GTV was provided with a 5 mm PTV expansion to account for slight changes in tumor motion and daily setup uncertainties as documented by Ruben et al9 Work by McCann66 and Chan51 have shown that such uncertainties can be accounted for with reduced tissue doses by escalating dose to the edges of the GTV. Therefore, a potentially ideal solution for future investigation is the optimization across the 4DCT dataset with intentional dose escalation at the maximum extent of travel.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, each GTV was provided with a 5 mm PTV expansion to account for slight changes in tumor motion and daily setup uncertainties as documented by Ruben et al9 Work by McCann66 and Chan51 have shown that such uncertainties can be accounted for with reduced tissue doses by escalating dose to the edges of the GTV. Therefore, a potentially ideal solution for future investigation is the optimization across the 4DCT dataset with intentional dose escalation at the maximum extent of travel.…”
Section: Discussionmentioning
confidence: 99%
“…An offline- re-planning strategy was presented by Bratengeier et al The technique adapts step and shoot intensity modulated radiotherapy plans by modifying only the segment shapes and preserving the monitor units [ 18 , 19 ]. Another approach would be to generate motion robust treatment plans that are robust against interfraction and intrafraction motion [ 20 , 21 ]. Online workflows have increased with the availability of in-room imaging systems like CT or MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Comments [49,50,51,52,53,54,55,56,57,58,59,60,61] Dose accumulation methodology [62,53,63,64,65,66,67,68,69,70,71,72,73,74] Intra-fraction accumulation [75,76,77,78,70,79,80,81,82,83,84,85,86,87,83,88,89,90] Interplay effect [66,91,92,93,94,95,…”
Section: Refmentioning
confidence: 99%